Comparison of the Dacron ring and suture annuloplasty for aortic root repair: an in vitro evaluation. (1st June 2018) - Sharghbin, Mona; Benhassen, Leila L; Lading, Troels; Bechsgaard, Tommy; Nielsen Skov, Søren; Røpcke, Diana M; Lyager Nielsen, Sten; Hasenkam, J Michael; Johansen, Peter
Abstract: OBJECTIVES: Increasing evidence shows that annular stabilization is essential in most aortic valve repair procedures. However, a standardized comparison of the 2 commonly used annuloplasty procedures is lacking. We hypothesized that the Dacron ring is more rigid than the polytetrafluoroethylene suture, whereas both procedures decrease annular dimensions. The aim of this study was to compare the biomechanical properties of the ring and suture techniques with native aortic roots in vitro . METHODS: Eighteen aortic roots explanted from 80-kg pigs were randomized into a Dacron ring group, a suture annuloplasty group and a native control group. Each sample was tested in a pulsatile in vitro model with a force transducer attached to the aortic annulus to obtain radial force measurements, and annular dynamics was evaluated using 2-dimensional echography. RESULTS: Among the 2 annuloplasty procedures, only the Dacron ring group provided a significant reduction in the annular diameter compared with the native group ( P  < 0.006). Both annuloplasty procedures significantly reduced the geometric orifice area, tenting area and sinus diameter while increasing the coaptation length compared with the native group. Systolic annular distension was retained between groups, although the total radial forces were significantly reduced in the procedure groups compared with the native group (ring 1.07 ± 0.45 N, suture 1.13 ± 0.39 N and native 3.55 ± 1.34 N, P  < 0.001). CONCLUSIONS: Although both annuloplasty procedures increase coaptation length and decrease geometric orifice area, a significant downsizing of the annulus was achieved using the Dacron ring only. The systolic annular distension was similar to the native aortic root, whereas the radial annular forces were evenly decreased by both annuloplasty procedures. Long-term studies are needed to disclose any difference in long-term effect of the annuloplasty procedures.